2016
DOI: 10.1098/rsif.2016.0506
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent fractional molecular diffusion in humid spider silk fibres

Abstract: Spider silk is a material well known for its outstanding mechanical properties, combining elasticity and tensile strength. The molecular mobility within the silk's polymer structure on the nanometre length scale importantly contributes to these macroscopic properties. We have therefore investigated the ensemble-averaged single-particle self-dynamics of the prevailing hydrogen atoms in humid spider dragline silk fibres on picosecond time scales in situ as a function of an externally applied tensile strain. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…It does rely, however, on some pre-existing fluctuations in the distribution of crystals, such that order should not arise from a fiber with a perfectly homogenous crystal distribution. The observed ordering effect is in line with the very recent observation by quasi-elastic neutron scattering experiments of spider silk that the diffusive mobility of the amorphous phase increases with tensile strain 31 . We propose that tensile forces present during the spinning process of silk or other synthetic fibers enhance long-range pre-order, which in turn boosts further ordering during tensile loading.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It does rely, however, on some pre-existing fluctuations in the distribution of crystals, such that order should not arise from a fiber with a perfectly homogenous crystal distribution. The observed ordering effect is in line with the very recent observation by quasi-elastic neutron scattering experiments of spider silk that the diffusive mobility of the amorphous phase increases with tensile strain 31 . We propose that tensile forces present during the spinning process of silk or other synthetic fibers enhance long-range pre-order, which in turn boosts further ordering during tensile loading.…”
Section: Discussionsupporting
confidence: 90%
“…Small-angle neutron scattering (SANS) was undertaken to test our computational prediction of stress-induced ordering in silk fibers. Deuterated fiber bundles using H/D exchange of Nephila edulis spider silk 23 , 31 were subjected to increasing values of constant strains, for each of which a SANS pattern was recorded. An increase in scattering peak intensity on the nanometer length scale upon fiber stretch would reflect a long-range order of crystalline units within the flexible and thus more strongly deuterated amorphous phase, which also includes a partially ordered phase around the non-deuterated crystallites 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 95 ] The mechanical properties of dragline silk are optimal in a suitable ambient environment, which changes drastically if the fibers are wet or in a high‐moisture environment. [ 96 ] Studies have found that water can disrupt the H‐bonds to increase the molecular mobility, so that the molecular entropy could drive the non‐crystalline regions to rearrange to lower energetic configurations. [ 13 , 97 ] When the relative humidity of spider silk exceeded 60%, the diameter of the spider dragline silk increased and the fiber length decreased by more than 50%, which is commonly referred to as supercontraction behavior.…”
Section: Other Physical Properties Of the Spider Silk And The Inspire...mentioning
confidence: 99%
“…where R is the spectrometer resolution function, β, β L(Γ(q) + γ(q), ω) may be replaced by a more general function such as a generalized model of internal diffusivity [5,43], the Fourier transform of a Kohlrausch [4,16,44,45] or Mittag-Leffler [46,47,48] function, or the result of a molecular dynamics simulation, if applicable. In reported backscattering experiments on protein solutions, the apparent center-of-mass diffusion was consistent with simple Brownian diffusion, γ(q) = D q 2 [9,15,17,19].…”
Section: Introductionmentioning
confidence: 99%